Digital Entrepreneur Ecosystem for Digital Economy. - ALYA SYAZANA, YUMAT (Universiti Malaysia Sarawak (UNIMAS), 2019)
Nowadays, the economy can be digitalized by adopting and utilizing digital technologies in transaction, services, communication and other core functions to gain more productivity, revenue and income as stated by MDEC. Sarawak government has started focusing on digital economy for Sarawak’s economy development. The entrepreneurship is normally started with a small business and in this digital economy era, the Digital Entrepreneurship is becoming a trend. There are changes in the business operations and practices due to the rapid growth of technologies. Besides, there might have several new policies for digital entrepreneurship. The changes and the details of the digital entrepreneur will be recorded in a clear, simple and visually appealing ecosystem through this research.